Towards effective implementation of children's rights in Tanzania: lessons and opportunities from Ghana and South Africa - Dowuona-Hammond, Christine (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2006.